TIPOLOGI TANAMAN PENAHAN EROSI ( Studi Kasus di Hutan Jati ) - B. Wisnu Widjajani (Universitas Trunojoyo Madura, 2010)
Natural disasters landslides often occurs recent years. Landslide occurrence related to the components of water, soil and plants, so understanding the typology of plants is important. Measurement of soil loss, plant factor is calculated based on the type and stage of plant growth, but the typology of plants have not much discussed. The purpose of this research to study the relationship of plants typology with soil loss rate in the teak forest system. The benefits of this research for the selection of plants in order to suppress loss of land, especially landslides. The results showed that the typology of plants which have dense canopies lower kinetic energy of rain could suppress loss of land. Vetivera zizanoides is an example of the most efficient plants. Crop coefficient of this plant produced as much as 0.03.